2023
DOI: 10.3390/pharmaceutics15020364
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Solute Carrier Transporters in Efficient Anticancer Drug Delivery and Therapy

Abstract: Transporter-mediated drug resistance is a major obstacle in anticancer drug delivery and a key reason for cancer drug therapy failure. Membrane solute carrier (SLC) transporters play a crucial role in the cellular uptake of drugs. The expression and function of the SLC transporters can be down-regulated in cancer cells, which limits the uptake of drugs into the tumor cells, resulting in the inefficiency of the drug therapy. In this review, we summarize the current understanding of low-SLC-transporter-expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 327 publications
0
13
0
Order By: Relevance
“…Transporters play an important role in the modulation of metabolism and ion homeostasis of tumor cells, both important factors in proliferation, apoptosis, hypoxia, and migration [ 15 ]. SLC transporters represent a plethora of new therapeutic targets for rare diseases and many metabolic disorders by being amenable to targeting small molecules [ 11 , 17 ]. Importantly, many SLC transporters are expressed on the cell surface and therefore could be targeted by small molecules and therapeutic antibodies [ 15 , 131 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transporters play an important role in the modulation of metabolism and ion homeostasis of tumor cells, both important factors in proliferation, apoptosis, hypoxia, and migration [ 15 ]. SLC transporters represent a plethora of new therapeutic targets for rare diseases and many metabolic disorders by being amenable to targeting small molecules [ 11 , 17 ]. Importantly, many SLC transporters are expressed on the cell surface and therefore could be targeted by small molecules and therapeutic antibodies [ 15 , 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…SLC transporters facilitate the entry of diverse metabolically significant substrates into cells, which is essential for human physiology. These processes include glucose absorption, uptake of water-soluble vitamins crucial for vital functions, transportation of metal ions, amino acid intake in the intestine, and reabsorption of neurotransmitters into presynaptic neurons [ 11 ]. Tumorigenesis, a complex process, orchestrates the conversion of normal cells into highly malignant derivatives [ 12 , 13 ].…”
Section: Slc Transporters In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies using brain metastasis mouse models have shown that the heterogeneity of the BTB significantly affects the concentration and distribution of drugs in the tumor ( 53 ). Currently, clinical treatment methods and strategies are actively being developed to promote the bypass of drugs through the brain barrier and improve drug penetration and increase blood concentration in the brain ( 54 ).…”
Section: Mechanism Of Gc Brain Metastasismentioning
confidence: 99%
“…OCT1 is mainly involved in the hepatic uptake of various drugs, toxins, and endogenous substrates [9][10][11][12]. Similarly, OATP1A2 is also involved in the transport of a wide variety of xenobiotics including anticancer drugs and endogenous substrates [13]. These transporters regulate the in ux of substrates through electrochemical gradients across the membrane [7].…”
Section: Introductionmentioning
confidence: 99%